Treasure island: level 3 - Stevenson, Robert Louis; Robert Louis Stevenson (New Delhi Rising Sun, 2005)
a terrified Billy Bones struggles with alcohol withdrawal and hallucinations after a visit from Black Dog.
Keywords: focuses on the deteriorating condition of the captain; the destructive nature of greed, the importance of personal integrity